Quantitative determination of buprenorphine, naloxone and their metabolites in rat plasma using hydrophilic interaction liquid chromatography coupled with tandem mass spectrometry. (22nd August 2016) - Joshi, Anand; Parris, Brian; Liu, Yongzhen; Heidbreder, Christian; Gerk, Phillip M.; Halquist, Matthew
Abstract: A rapid and sensitive LC–MS/MS method was developed and validated for the simultaneous determination of buprenorphine and its three metabolites (buprenorphine glucuronide, norbuprenorphine and norbuprenorphine glucuronide) as well as naloxone and its metabolite naloxone glucuronide in the rat plasma. A hydrophilic interaction chromatography column and a mobile phase containing acetonitrile and ammonium formate buffer (pH 3.5) were used for the chromatographic separation. Mass spectrometric detection was achieved by an electrospray ionization source in the positive mode coupled to a triple quadrupole mass analyzer. The calibration curves for the six analytes displayed good linearity over the concentration range 1.0 or 5.0–1000 ng/mL. The intra and inter‐day precision (CV) ranged from 2.68 to 16.4% and from 9.02 to 14.5%, respectively. The intra‐ and inter‐day accuracy (bias) ranged from −14.2 to 15.2% and from −9.00 to 4.80%, respectively. The extraction recoveries for all the analytes ranged from 55 to 86.9%. The LC–MS/MS method was successfully applied to a pharmacokinetic study of buprenorphine–naloxone combination in rats.